Spraying Disinfectants to Combat SARS-CoV-2 Transmission: Is it Fruitless Rather Than Fruitful? - Md Sohel, -; Mahmod, Md Rashel (Bangladesh Journal of Infectious Diseases, 2021)
Abstract not available Bangladesh Journal of Infectious Diseases 2020;7(2):113-114